House ownership and taxes - Torfinn Harding; Haakon O. Aa. Solheim; Andreas Benedictow (Statistics Norway, Research Department, 2004)
The household portfolio is dominated by a small number of assets; primarily housing and mortgages. We compare data on actual portfolios of Norwegian households with estimated optimal portfolios, using traditional financial theory. We find actual portfolios to be close to the portfolio indicated by a mean-variance frontier, based on four assets and estimated under assumptions of short sale constraints. This result is sustained even in a no-tax regime. To induce a substantial change from housing to equity, taxation of the consumption stream from housing is needed. An alternative; taxation of capital gains from housing investment; could actually increase the relative holding of housing.
Keywords: G11; H2; H31; 330; Households; portfolio choice; consumption tax; capital gains tax.